Complementarity in Employee Participation Systems: International Evidence - Gabriel Burdin; Takao Kato (Institute of Labor Economics (IZA), 2021)
We describe the nature, scope and effects of various non-mandated participatory work practices in Japan, the U.S. and Europe through the lens of complementarity in organizations. Specifically, rather than treating each work practice in isolation, we consider it an element of HIWS (High Involvement Work System), an employment system comprised of clusters of complementary work practices. In so doing, we present a coherent and complete picture of non-mandatory participatory work practices. Furthermore, by applying the common framework of viewing participatory work practices as complementary elements of HIWS to seemingly disparate forms of work practices in different parts of the world, we shed light on how participatory work practices play out in diverse institutional, cultural and regulatory environments.
Keywords: M5; J5; 330; High Involvement Work System; High Performance Work System; employee participation